2001
DOI: 10.1080/03075070120076318
|View full text |Cite
|
Sign up to set email alerts
|

Making Ends Meet: Student incomes and debt

Abstract: This article seeks to explore the ways in which the current nancial regime for supporting students impacts on the choices they make while studying for their rst degree. It focuses particularly on the nancial choices students make (or feel forced to make) in relation to work, debt and economising. It argues that the degree of discretion that students have is crucially related to the nancial support they receive from their parents. However, even where parents are generous, most students seek an additional source… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 20 publications
3
48
0
3
Order By: Relevance
“…MaryAnn supplemented her income by working during term time, a situation that her father was 'cross about' but preferable to the fact that he 'would kill her' if she took out a loan. Almost all of the students in this group attributed at least part of their debt aversion to the views of their parents (Christie et al, 2001). Andrew (Edinburgh) juggled money from various sources, including £200/month from his parents, and explained why he did not borrow: from the advice of my brothers and sisters mainly and my Dad said 'if you can, don't … because it's better not to get into debt' and I haven't needed them.…”
Section: The Decision To Attend Universitymentioning
confidence: 98%
See 1 more Smart Citation
“…MaryAnn supplemented her income by working during term time, a situation that her father was 'cross about' but preferable to the fact that he 'would kill her' if she took out a loan. Almost all of the students in this group attributed at least part of their debt aversion to the views of their parents (Christie et al, 2001). Andrew (Edinburgh) juggled money from various sources, including £200/month from his parents, and explained why he did not borrow: from the advice of my brothers and sisters mainly and my Dad said 'if you can, don't … because it's better not to get into debt' and I haven't needed them.…”
Section: The Decision To Attend Universitymentioning
confidence: 98%
“…With a few exceptions, the introduction of loans and fees has not turned students into purely individual contractors. If anything, the removal of grant support has tightened the financial link between parents and students (Christie et al, 2001). The assumed availability of financial support from parents underpins the means-testing for tuition fees and to part of the student loan.…”
Section: Family Resources and Social Class Differencesmentioning
confidence: 99%
“…In a more recent study, Johnston [36] provides evidence to suggest that working about 12 hours or more a week tends to impact negatively on performance, with lower levels of employment having a negligible impact. Christie et al [37] conclude that while, in general, students appear to cope reasonably well with indebtedness and part-time employment, there were clear differences between various categories of students. In particular, and not surprisingly, students with parental support coped markedly better than those without.…”
Section: Part-time Paid Employmentmentioning
confidence: 99%
“…Hesketh, 1999;Callender & Kemp, 2000;Christie et al, 2001). The students in this study had attempted to live frugally, but generally found that they were compelled to take on paid work in order to make ends meet, placing pressure on their studies (Hutchings, 2003;Forsyth & Furlong, 2003;Hunt et al, 2004;Quinn et al, 2005) :…”
Section: Financial Supportmentioning
confidence: 99%